Blanching induced effect on bioactive compounds and anti-diabetic properties of bitter gourd - Ojha, Pravin; Kafley, Akash (Journal of Food Science and Technology Nepal, 2024)
The purpose of the study was to determine how pretreatment techniques, such as blanching in hot water or alkaline solution, affected the bioactive ingredients, and anti-diabetic properties of bitter gourd. The bitter gourd was blanched in hot water and an alkaline solution (a mixture of saturated magnesium oxide and 0.1% sodium carbonate) at 98 °C for three minutes. Both pretreated bitter gourds were submerged in a 5% salt solution for 1 hour. Untreated fresh bitter gourd was used as the control. Ascorbic acid levels (mg/100g) and antioxidant activity (DPPH inhibition %) were dramatically (p